2013
DOI: 10.1149/05043.0085ecst
|View full text |Cite
|
Sign up to set email alerts
|

EQCM Investigation on Electrodeposition and Charge Storage Behavior of Birnessite-Type MnO2

Abstract: We have fabricated birnessite-type layered manganese oxide bycathodic reduction of aqueous permanganate ions (MnO4-) in thepresence of various alkaline metals. The electrodeposition andcharge storage processes were monitored by means ofelectrochemical quartz crystal microbalance (EQCM). Molarmasses acquired for the electrodeposition process revealed thatMnO2 grows concurrently with the incorporation of the coexistingcations and water molecules. The molar mass decreases in theorder of Li > Rb ~ K ~ Cs > N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…12,14,15,32,34 More recent EQCM reports examined MnOx pseudocapacitance phenomena and showed that cation insertion and ejection during reduction and oxidation, respectively, is the primary charge-compensation mechanism. 16,32,35 Traditional quartz crystal microbalance (QCM) experiments rely on the assumption that films are acoustically thin, thus allowing for gravimetric interpretation of the results using the Sauerbrey equation. Here, we first examine the EQCM behavior of electrodeposited Na-birnessite-type MnOx films, which we select as a thin-film mimic of the birnessite-MnOx coatings present in the carbon nanofoams.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…12,14,15,32,34 More recent EQCM reports examined MnOx pseudocapacitance phenomena and showed that cation insertion and ejection during reduction and oxidation, respectively, is the primary charge-compensation mechanism. 16,32,35 Traditional quartz crystal microbalance (QCM) experiments rely on the assumption that films are acoustically thin, thus allowing for gravimetric interpretation of the results using the Sauerbrey equation. Here, we first examine the EQCM behavior of electrodeposited Na-birnessite-type MnOx films, which we select as a thin-film mimic of the birnessite-MnOx coatings present in the carbon nanofoams.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of Na-birnessite-type MnO 2 thin films.-Electrochemical quartz microbalance methods have been previously used to study MnOx, with most reports focused on analyzing the electrodeposition process of MnOx thin films. 12,14,15,32,34 More recent EQCM reports examined MnOx pseudocapacitance phenomena and showed that cation insertion and ejection during reduction and oxidation, respectively, is the primary charge-compensation mechanism. 16,32,35 Traditional quartz crystal microbalance (QCM) experiments rely on the assumption that films are acoustically thin, thus allowing for gravimetric interpretation of the results using the Sauerbrey equation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To construct better SCs, it is of great importance to understand the charge storage mechanisms of these materials at molecular level. Recently, electrochemical quartz crystal microbalance (EQCM) as an in situ experimental methodology has started to address the charge storage mechanisms of SCs, thanks to its super‐sensitive change in the gravimetry (10 −9 g) and thickness during charging and discharging process …”
Section: Introductionmentioning
confidence: 99%